Isolation and identification of indole acetic acid producing bacteria from the coasts of Ben Tre and Tra Vinh Provinces - Lan, Nguyen Ngoc; Dzung, Vu Van; Lien, Nguyen Thi Kim; Thoa, Nguyen Kim; Nghi, Do Huu; Hoang, Nguyen Huy (Academia Journal of Biology, 2019)
Beneficial plant-growth-promoting bacteria (PGPB) have been reasonably applied to rescue crucial issue for agriculture by salinity soil. Observed most of PGPB was found in endophyte, rhizosphere and soil. Indole acetic acid (IAA)-producing bacteria could naturally stimulate and facilitate plant growth. The knowledge of IAA production and content of bacteria resident in the marine environment has been typically insufficient and limited to date. In recent years, unwarrantable intrusions of sea water have been enlarged in the Mekong River Delta of Vietnam, threatening productive rice fields, local fruits, and cash crops. Therefore, finding PGPB in the coastal regions in the Mekong River Delta as a creative resource for sustainable agriculture is necessary and is a prompt challenge. In this study, IAA-producing bacteria from coastal regions of Ben Tre and Tra Vinh Provinces were isolated and adequately identified. Out of 202 bacterial isolates, 10 isolates showed the possible ability to produce IAA from L-tryptophan. These 10 isolates were objectively evaluated the capacity to produce IAA under 5% (w/v) NaCl in King B and marine broths. The results revealed that IAA production decreased in 5% NaCl, even though bacterial growth increased. These 10 IAA-producing bacteria were classified at the species level, Marinobacter hydrocarbonoclasticus, M. pelagius, M. daepoensis, and Mameliella phaeodactyli by 16S rRNA gene analysis. The most IAA producer in King’s B broth, the isolate C7, was investigated in more detail. The isolate C7 produced the maximum IAA amount (192.2 ± 1.14 µg/ml) under the presence of 20 g/l yeast extract, 2 g/l of L-tryptophan and 1% NaCl. The isolate C7 was able to grow at 1–17% (w/v) NaCl (optimum, 4%), but not in the absence of NaCl, indicating it is a moderate halophilic bacteria. This study highlighted the considerable ability to produce IAA of marine bacteria, which could be thoughtfully considered to use naturally as biofertilizers to promote plant growth in saline intrusion lands.